The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/23259671221077679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgeon Experience on Long-Term Patient Outcomes in Surgical Repair of Acute Achilles Tendon Rupture

Abstract: Background: The effect of surgeon experience on patient outcomes after surgical Achilles tendon rupture (ATR) repair has so far been unknown. Purpose: To examine whether patient-reported and functional outcomes as well as adverse events after surgical ATR repair differ between orthopaedic specialist surgeons and resident surgeons. Study Design: Cohort study; Level of evidence, 3. Methods: We retrospectively analyzed data from 295 patients treated with surgical ATR repair with standardized techniques. The level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Participant height and body mass were measured, and BMI calculated. Previous follow‐up studies using similar methods have reported sample sizes of 22–86 individuals [4–6], and we aimed to include similar numbers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participant height and body mass were measured, and BMI calculated. Previous follow‐up studies using similar methods have reported sample sizes of 22–86 individuals [4–6], and we aimed to include similar numbers.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, our aim was to assess whether early symmetry of AT and triceps surae muscle properties at 2 months after rupture were associated with side‐to‐side symmetry in isometric plantarflexor maximal voluntary contraction (MVC) and AT nonuniformity at 6 and 12 months. We examined whether participant age [3], sex [3], early symmetry of MG muscle and AT architecture [2, 4–7], ATRA [8, 15–17], or AT shear wave velocity (SWV, m × s −1 ) [7] measured at 2 months postinjury would serve as potential predictors of MVC and AT nonuniformity. We hypothesized that younger age and better structural and mechanical symmetry at 2 months would be related to better symmetry of MVC and AT nonuniformity at 6 and 12 months.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above discussion is relevant to tendon repair as after surgery, the affected limb is usually immobilized for various periods of time and thus, subjected to conditions that foster atrophy of muscle bone and the surgically repaired AT. This may also affect the vascular system as such patients may incur a deep vein thrombosis at a high rate [~50%; discussed in Saarensilta et al (2023b)]. However, this immobilization is occurring after surgery and based on the proteomic studies (Chen et al, 2022;Chen et al, 2023;Wu et al, 2023), biomarkers of good outcomes at 1-year were already evident prior to surgery.…”
Section: The Wound Healing Environment After An Acute Tendon Injurymentioning
confidence: 99%